2015
DOI: 10.1530/ec-14-0119
|View full text |Cite
|
Sign up to set email alerts
|

Bone metastases and skeletal-related events from neuroendocrine tumors

Abstract: Neuroendocrine tumors (NETs) metastasize to bone; however, a multi-institution evaluation of the natural history and complications of bone metastases across multiple NET subtypes has not, to our knowledge, previously been conducted. At two tertiary academic centers, we identified patients with bone metastases from databases of patients with a diagnosis of NET between 2004 and 2008. Detection of bone metastases, occurrence of skeletal-related events (SREs), and interventions were analyzed using summary statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
109
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(126 citation statements)
references
References 15 publications
11
109
3
3
Order By: Relevance
“…In the present study a significant difference in median survival was observed between patients with bone metastases and those with soft-tissue metastases (59.6 vs. 84.1 mo, P , 0.0001); median survival for those without metastatic disease was 96.7 mo. Our findings are in agreement with a recent study in which median survival for patients with both liver and bone metastases from NETs was 15.4-62.1 mo, compared with 18.2-166.3 mo in patients with liver metastases and no detected bone metastases (P , 0.0001), the variations depending on histologic subtype and grade of differentiation (24).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study a significant difference in median survival was observed between patients with bone metastases and those with soft-tissue metastases (59.6 vs. 84.1 mo, P , 0.0001); median survival for those without metastatic disease was 96.7 mo. Our findings are in agreement with a recent study in which median survival for patients with both liver and bone metastases from NETs was 15.4-62.1 mo, compared with 18.2-166.3 mo in patients with liver metastases and no detected bone metastases (P , 0.0001), the variations depending on histologic subtype and grade of differentiation (24).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we did not attempt to correlate the SUV, as a semiquantitative marker of SSTR expression, with survival, as it is part of a separate study. Bone metastases were once considered exceedingly rare in patients with NETs but more recent studies have shown that they may be detected in 12% of overall NET populations and approximately 25% in some subgroups (24). In the present study a significant difference in median survival was observed between patients with bone metastases and those with soft-tissue metastases (59.6 vs. 84.1 mo, P , 0.0001); median survival for those without metastatic disease was 96.7 mo.…”
Section: Discussionmentioning
confidence: 99%
“…Metastases are predominantly found in the liver and/or lymph nodes. In contrast, bone metastases are reported in <15% of cases [5,6]; however, the true prevalence of bony metastases is probably underestimated, since the reported figures are not based on the most sensitive imaging methods such as bone MRI or 68 Ga-DOTATOC/NOC/TATE PET/CT. Other rare disease sites include the lung, brain and peritoneum, which have also been covered in guidelines [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although in a small postmortem study bone involvement was found in 42% of patients [9], the clinical detection of skeletal metastases is usually reported in <18% of patients with advanced disease [10,11,12,13,14]. Foregut and hindgut tumors are apparently prone to metastasize to the bone as compared with midgut carcinoids [8,15,16], although no preferential primary tumor site has been identified in a recent retrospective study [14].…”
Section: Introductionmentioning
confidence: 99%
“…Foregut and hindgut tumors are apparently prone to metastasize to the bone as compared with midgut carcinoids [8,15,16], although no preferential primary tumor site has been identified in a recent retrospective study [14]. Skeletal metastases are asymptomatic in 40% of patients [13] and are usually discovered incidentally during tumor staging [11]. However, they result in significant morbidity and severely reduce quality of life due to the emergence of skeletal-related events (SREs), such as pathological fractures, spinal cord compression, need for orthopedic surgery or radiotherapy to bone and/or hypercalcemia [13].…”
Section: Introductionmentioning
confidence: 99%